2018
DOI: 10.1016/j.tecto.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Reflection seismic images and amplitude ratio modelling of the Chilean subduction zone at 38.25°S

Abstract: Active source near-vertical reflection (NVR) data from the interdisciplinary project TIPTEQ were used to image and identify structural and petrophysical properties within the Chilean subduction zone at 38.25 • S, where in 1960 the largest earthquake ever recorded (M w 9.5) occurred. Reflection seismic images of the subduction zone were obtained using the post-stack depth migration technique to process the three components of the NVR data, allowing to present P-and S-stacked time sections and depth-migrated sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The map shows ocean-continent subduction zones around the Circum-Pacific region with emphasis on segments where tectonic underplating is suspected, based on geophysical observations. (1) Hikurangi margin [64][65][66] , (2) Nankai margin 67 , (3) Sagami trough 23 , (4) Alaska margin 68,69 , (5) Cascadia margin [70][71][72] , (6) Costa Rica margin 73 , (7) North Chilean margin 74,75 and (8) Central Chilean margin 74,[76][77][78][79] . Black frames locate regions where trench-perpendicular topographic profiles have been compiled.…”
mentioning
confidence: 99%
“…The map shows ocean-continent subduction zones around the Circum-Pacific region with emphasis on segments where tectonic underplating is suspected, based on geophysical observations. (1) Hikurangi margin [64][65][66] , (2) Nankai margin 67 , (3) Sagami trough 23 , (4) Alaska margin 68,69 , (5) Cascadia margin [70][71][72] , (6) Costa Rica margin 73 , (7) North Chilean margin 74,75 and (8) Central Chilean margin 74,[76][77][78][79] . Black frames locate regions where trench-perpendicular topographic profiles have been compiled.…”
mentioning
confidence: 99%
“…(2006) and Ramos et al. (2018), which is the only deep seismic section generated in the onshore forearc of the study zone and is located along the track of profile P2. Krawczyk et al.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…10.1029/2021JB021879 Segmented blue lines are the main reflectors identified in the image behind, which corresponds to the onshore reflection seismic section presented by Krawczyk et al (2006). Black dots are the upper plate seismicity located by Haberland et al (2006) and segmented red line is the geometry of Lanalhue Faut Zone (LFZ) inferred by Ramos et al (2018) To complement a regional structural analysis, in Figure 8a, we project all segments of deep reflectors according to their position with respect to the deformation front. Because of the large distance between seismic profiles, the objective of this analysis is to study the structural style of the continental wedge at large scale, rather than the north-south continuity of specific reflectors.…”
Section: Geometrical Pattern Of the Modeled Deep Reflectorsmentioning
confidence: 99%
“…Gravity modelling techniques does not define a downward limit of WS/ES (without independent deep constraints). Nevertheless, interpretations of seismic reflection data at ~38.25ºS (Krawczyk et al, 2006;Ramos et al, 2018) showed the downward prolongation of WS/ES reaching deep levels near continental Moho interface (~30km depth). As previously mentioned, the seaward limit of WS/ES is not defined by direct lithological observations; their presence beneath the shelf basin is confirmed by 405 exploration boreholes (González, 1989).…”
Section: Interpretations and Discussionmentioning
confidence: 99%
“…At the same time, according to Menant et al (2019), the deformation style of basal accrationary complexes (typically an antiformal stack of duplexes) favoured upward fluid fluxes from the interplate boundary, generating dewatering and the increase of µb* in some adjacent regions of the subduction channel (mainly downward from basal accretionary complex). Several authors have siggested the presence of this deformation style in the deep zone of WS unit (Krawczyk et al, 2006;Ramos et al, 2018, Moreno et al 2018Maksymowicz et al, submitted 495 for publication). Under this interpretation, the widening of MWU and CC domains to the north of ~42ºS could favoured high friction in the deep region of interplate boundary (bellow CC domain) and a relatively low friction in the seaward portion of MWU.…”
mentioning
confidence: 99%